MINI-REVIEW: PEMBUATAN DYE-SENSITIZED SOLAR CELLS (DSSC) MENGGUNAKAN SEMIKONDUKTOR TIO2 DENGAN BANTUAN ZAT PEWARNA ALAMI - Muhammad Irvan Mulya Pratama; Veliyana London Allo; Noor Hindryawati (PROSIDING SEMINAR KIMIA, 2022)
The availability of energy sources such as coal and oil is getting thinner every year. Sunlight is one of the most abundant sources of energy on earth. Solar cells can convert this energy into electricity and over time, dye-Sensitized solar cells (DSSC) have the potential to be developed because they have good efficiency. However, the use of synthetic dyes is difficult to obtain and is toxic because it contains heavy metals. Therefore, natural dyes are used as alternative materials in the fabrication of DSSC. The purpose of this article is to review the results of research on DSSC using natural dyes. The method used in this research is the literature review method. The results of the literature review show that the DSSC made with TiO2 semiconductor and natural dyes has a good efficiency of about 0,592 %. Natural dyes can be obtained by extracting plants containing anthocyanins, curcumin and chlorophyll such as red cabbage, turmeric and pandan leaves, what's interesting is that using 2 different types of natural dyes will produce higher efficiency than 1 type of dye. In addition, treatment factors such as dye extraction, the amount of TiO2 used and the length of immersion into the dye also affect the efficiency of the DSSC. Keywords: DSSC, natural dyes and efficiency